2020
DOI: 10.1186/s12886-019-1289-5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intraretinal fluid observed using optical coherence tomography in the epiretinal membrane

Abstract: Background: Postoperative intraretinal fluid (IRF) is reportedly associated with visual outcomes after epiretinal membrane (ERM) surgery. However, preoperative IRF is common, and persistent IRF would have different impact on visual function from postoperative newly developed IRF. Therefore, we aimed to investigate the incidence rate and clinical implications of perioperative IRF in ERM. Methods: Medical records of patients who underwent vitrectomy for idiopathic ERM between January 2014 and January 2017 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…It has also been described in chronic retinal pathologies 6 or after vitrectomy for epimacular membrane. 11–16. Dormegny et al 7 also reported this pattern of cysts with a high prevalence (48%) after retinal surgery with SO tamponade.…”
Section: Discussionmentioning
confidence: 80%
“…It has also been described in chronic retinal pathologies 6 or after vitrectomy for epimacular membrane. 11–16. Dormegny et al 7 also reported this pattern of cysts with a high prevalence (48%) after retinal surgery with SO tamponade.…”
Section: Discussionmentioning
confidence: 80%
“…IRC is also known as microcyst, cystoid macular edema (CME), intraretinal fluid, and schisis cavity in iERM. 5,14,17,18,25 Its prevalence ranged from 5.5% to 54.0% in previous studies, which is possibly attributable to the difference in methodology, including the OCT scan protocol for detection of IRC. Regarding the pathogenesis of ERM, tangential traction from Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Such discrepancy arose from differences in the methodology, including the OCT scan protocol (e.g., raster scan, radial scan, or volume scan) and the area under assessment for the affected lesion. 5,14,17,18,[23][24][25] Some studies were only conducted in the localized foveal or parafoveal region. 16,18,19,23 Limited assessment of a small region using a line scan may limit our understanding of the clinical significance of IRC in iERM.…”
mentioning
confidence: 99%
See 2 more Smart Citations